Symmetry in graptolite zooids and tubaria (Pterobranchia, Hemichordata). Issue 6 (14th December 2021) - Maletz, Jörg
Abstract: Extant and fossil pterobranchs show distinct symmetry conditions of the individual zooids and their tubaria that are not necessarily comparable. The strict bilateral symmetry in the zooids of extant Cephalodiscida is modified to a considerable anatomical asymmetry in extant Rhabdopleurida. This type of left–right asymmetry can be recognized as antisymmetry, as dextral and sinistral developments are equally common. Antisymmetry is also recognized in the rhabdopleurid tubaria and in the proximal development and branching of planktic graptoloids. The antisymmetry of the graptoloid tubarium is modified during the Tremadocian time interval to a fixed or directional asymmetry. From the latest Tremadocian or earliest Floian onwards, proximal development in the Graptoloidea is invariably dextral and very few examples of a sinistral development have been found. The transition from antisymmetry to directional asymmetry can only be recognized in the graptolite tubaria, as the anatomy of the zooids is unknown from the fossil record. Directional asymmetry is not recognized in extant Pterobranchia. Abstract : Research highlights: The original antisymmetry of the graptolites (Pterobranchia, Hemichordata) evolved to a directional asymmetry with invariably dextral development, recognized from fossil taxa. Directional asymmetry is not recognized in extant Pterobranchia.